DETERMINATION OF RANGE OF FUSION OF ECTOCRANIAL SKULL SUTURES FOR DETERMINATION OF AGE IN SAURASHTRA REGION OF GUJARAT (Journal of Forensic Medicine & Toxicology, 2019)
Background: Identification is the determination of individuality of a person based on certain physical characteristic. Identification of individual is important when body found is decomposed, mutilated or unidentified in cases like vehicular accidents, train accidents, plane accidents, earthquakes,floods, ship braking and other mass disasters. Determination of age from skull suture plays important role in identification of individual. The study is done for the determination of age from the closure of skull sutures. Method: 220 cases were selected randomly from the dead bodies brought to the mortuary at P. D. U. Government Medical College & hospital, Rajkot. The cross sectional study was to determine closure of skull sutures. The closure of sutures were categorized in open suture, in process of fusion and fused sutures. The collected data was categorized and analyzed and tables were prepared. Result:Majority cases of sagittal sutures are fused in first and second part by the age of 54 years, fused in third part by the age of 59 years and fused in fourth part by the age of 44 years. In majority cases of coronal sutures, first parts were found fused by the age of 59 years, second parts were found fused by the age of 49 years and third parts were found fused by the age of 49 years. In majority cases of lambdoid sutures, first parts were found fused by the age of 59 years, second parts were found fused by the age of 64 years and third parts were found fused by the age of 69 years. Conclusion: Range of fusion of ectocranial sagittal sutures in first and second part is 40 to 54 years, in third part 40 to 59 years and in fourth part 25 to 44 years. Range of fusion of ectocranial coronal sutures in first part is 45 to 59 years, in second part 35 to 49 years and in third part 50 to 59 years. Range of fusion of ectocranial lambdoid suture in first part is 50 to 59 years, in second part 50 to 64 years and in third part 60 to 69 years.
Keywords: mutilation; fusion; Rajkot; dismembered